Proteomic analysis of the thermophilic methylotroph Bacillus methanolicus MGA3. Issue 6 (20th February 2014) - Müller, Jonas E. N.; Litsanov, Boris; Bortfeld‐Miller, Miriam; Trachsel, Christian; Grossmann, Jonas; Brautaset, Trygve; Vorholt, Julia A.
Abstract : Bacillus methanolicus MGA3 is a facultative methylotroph of industrial relevance that is able to grow on methanol as its sole source of carbon and energy. The Gram‐positive bacterium possesses a soluble NAD + ‐dependent methanol dehydrogenase and assimilates formaldehyde via the ribulose monophosphate (RuMP) cycle. We used label‐free quantitative proteomics to generate reference proteome data for this bacterium and compared the proteome of B. methanolicus MGA3 on two different carbon sources (methanol and mannitol) as well as two different growth temperatures (50°C and 37°C). From a total of approximately 1200 different detected proteins, approximately 1000 of these were used for quantification. While the levels of 213 proteins were significantly different at the two growth temperatures tested, the levels of 109 proteins changed significantly when cells were grown on different carbon sources. The carbon source strongly affected the synthesis of enzymes related to carbon metabolism, and in particular, both dissimilatory and assimilatory RuMP cycle enzyme levels were elevated during growth on methanol compared to mannitol. Our data also indicate that B. methanolicus has a functional tricarboxylic acid cycle, the proteins of which are differentially regulated on mannitol and methanol. Other proteins presumed to be involved in growth on methanol were constitutively expressed under the different growth conditions. All MS data have been deposited in the ProteomeXchange with the identifiers PXD000637 and PXD000638 (http://proteomecentral.proteomexchange.org/dataset/PXD000637, http://proteomecentral.proteomexchange.org/dataset/PXD000638 ).